The wrong side of goodbye : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch series., 2016)
California's newest private investigator, Harry Bosch, searches for a reclusive billionaire's possible heir, a case with odd links to his own past, and volunteers to find a serial rapist for a small cash-strapped police department.